Preparation method of modified electrode for all-vanadium redox flow battery and all-vanadium redox flow battery

By soaking the graphite felt electrode in an ammonium salt solution and performing high temperature activation, the problem of high cost and unstable performance of the electrode electrode material of all vanadium flow battery is solved, efficient modification of the electrode is achieved, the energy efficiency and power density of the battery are improved, and stable operation is maintained under high current density.

CN119786628AActive Publication Date: 2025-04-08CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510091969.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-08
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The electrode materials of existing all-vanadium flow batteries are costly, and the modification method has environmental protection problems and unstable electrode performance.

Method used

The method of soaking the graphite felt electrode in an ammonium salt solution and performing high-temperature activation is adopted to improve the hydrophilicity and electrochemical properties of the electrode by changing the micromorphology of the surface of carbon fibers, increasing the specific surface area and reactive sites.

Benefits of technology

It improves the electrochemical active area and structural stability of the electrode, increases the vanadium ion reaction rate, reduces the energy loss during the charge and discharge process, improves the energy efficiency and power density of the all-vanadium flow battery, and maintains a long-term stable operation at higher current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786628A_ABST
    Figure CN119786628A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of redox flow batteries, and discloses a preparation method of a modified electrode for an all-vanadium redox flow battery. The preparation method comprises the following steps: soaking a graphite felt electrode in an ammonium salt solution; and then putting the graphite felt electrode soaked with the ammonium salt into a quartz tube of a tubular furnace for high-temperature activation to obtain the modified electrode. The invention also discloses an all-vanadium redox flow battery comprising the modified electrode. The modified electrode prepared by the invention has the characteristics of large electrochemical active area, abundant active sites, stable structure and excellent performance, can enable the flow battery to operate at higher current density, and greatly improves the power density of the flow battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid flow batteries, and in particular relates to a method for preparing a modified electrode for an all-vanadium liquid flow battery and an all-vanadium liquid flow battery. Background Art

[0002] All-vanadium liquid flow batteries meet the characteristics required for long-term energy storage devices. All-vanadium liquid flow battery energy storage systems have outstanding advantages such as intrinsic safety, reliable operation, and environmental friendliness throughout the entire life cycle. Their output power and energy storage capacity are independent of each other, and they are flexible in design and installation, making them suitable for large-scale, large-capacity, and long-term energy storage. They have high energy conversion efficiency, fast startup speed, no phase change, and rapid response to charge and discharge state switching. All-vanadium liquid flow battery energy storage systems adopt a modular design, which is easy for system integration and scale-up. However, the main factor restricting the development of all-vanadium liquid flow batteries is the cost issue. Reducing the cost and increasing the efficiency of key materials including electrodes, ion exchange membranes, and electrolytes is the key to reducing the cost of vanadium batteries.

[0003] Among them, the electrode is the key component of the all-vanadium redox flow battery, which is the active material in the electrolyte (VO 2+ / VO 2+ 、V 3+ / V 2+ ) provide a place for redox reactions to occur. Since the redox reaction of vanadium ions occurs on the surface of the two electrodes, the energy efficiency of the battery depends largely on the electrocatalytic performance of the electrodes. Graphite felt is the first choice for electrode materials because of its large specific surface area, good stability and good conductivity. However, the original graphite felt itself is hydrophobic, and due to the small number of active sites, the redox kinetics are poor, resulting in poor battery efficiency. Therefore, it is necessary to modify the graphite felt to improve the redox kinetics of vanadium ions on the graphite felt, reduce the polarization of the battery to improve energy efficiency, power density and electrolyte utilization, etc.

[0004] In order to solve the above problems, the current modification methods are mainly divided into intrinsic modification and catalyst loading modification. Intrinsic modification is further divided into heat treatment, acid treatment and electrochemical oxidation; catalyst loading modification mainly introduces metals, metal compounds, carbon-based materials and other materials that can enhance the electrode reaction activity or improve the electrode reaction selectivity into the electrode through physical or chemical methods. Commonly used intrinsic modification strategies such as acid treatment and alkali treatment will produce additional waste acid and alkali, which are difficult to recycle and cause waste of resources; after a long period of electrolyte flushing, the catalyst loaded modified electrode may cause the catalyst to fall off, causing electrolyte pollution. Therefore, it is necessary to study an electrode modification method that is environmentally friendly and has stable electrode performance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a method for preparing a modified electrode for an all-vanadium liquid flow battery and an all-vanadium liquid flow battery.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a modified electrode for an all-vanadium liquid flow battery comprises the following steps: (1) Soak the graphite felt electrode in an ammonium salt solution; (2) The graphite felt electrode soaked in ammonium salt after step (1) is placed in a quartz tube of a tubular furnace for high-temperature activation to obtain a modified electrode.

[0007] In the above-mentioned preparation method, preferably, in step (2), the graphite felt electrode soaked in ammonium salt is first placed in the non-insulation zone on one side of the quartz tube of the tubular furnace. After the tubular furnace is heated to 500-1000°C, the graphite felt electrode soaked in ammonium salt is pushed into the insulation zone to react for 5-60 minutes. The treatment process of the present invention causes the surface temperature of the graphite felt to rise sharply, thereby changing the microscopic morphology of the carbon fiber surface. This rapid change in temperature can create more defects (such as edge defects) and can more effectively achieve heteroatom doping. If it is directly placed in the temperature zone for heating, it will not only cause the ammonium salt to volatilize, but also be discharged with the air flow before doping and etching, resulting in the loss of ammonium salt, thereby reducing the doping source and etching source; moreover, the slow rise in temperature is not conducive to the change of the carbon fiber surface and the formation of defects.

[0008] In the above preparation method, preferably, in step (2), the high-temperature activation is carried out in an air atmosphere.

[0009] In the above preparation method, preferably, in step (1), the ammonium salt solution comprises ammonium salt, surfactant and water, wherein the concentration of the ammonium salt is 0.1-1.5 mol / L, and the mass ratio of the surfactant to water is 1:500-1:2000.

[0010] In the above preparation method, preferably, the ammonium salt is a soluble ammonium salt, including at least one of ammonium sulfate, ammonium carbonate, ammonium chloride, ammonium nitrate, ammonium phosphate, ammonium fluoride, ammonium bromide, ferrous ammonium sulfate, ammonium molybdate, ammonium tungstate, dodecyltrimethylammonium chloride, tetraethylammonium bromide, and ammonium acetate.

[0011] In the above preparation method, preferably, the surfactant includes at least one of Tween 20, Tween 40, Span 20, Span 40, and sodium dodecyl sulfate.

[0012] In the above preparation method, preferably, in step (1), the graphite felt electrode is polyacrylonitrile-based (PAN-based) graphite felt, asphalt-based graphite felt or viscose-based graphite felt.

[0013] Based on a general inventive concept, the present invention also provides an all-vanadium liquid flow battery, including a modified electrode prepared by the above-mentioned preparation method.

[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The modified electrode prepared by the present invention has the characteristics of large electrochemical active area, rich active sites, stable structure and excellent performance, which can enable the liquid flow battery to operate at a higher current density and greatly improve its power density.

[0015] (2) In the preparation process of the present invention, the electrode material is immersed in an ammonium salt solution and activated at high temperature to construct carbon defects, thereby improving the hydrophilicity of the electrode. High-temperature etching increases the specific surface area of ​​the electrode. Heteroatom doping produces abundant reactive sites on the electrode surface, thereby increasing the reaction rate of vanadium ions and reducing the energy loss during the charge and discharge process, so that the vanadium battery exhibits higher energy efficiency in the charge and discharge test. Moreover, the modified electrode has stable mechanical and electrochemical properties, so that the liquid flow battery can operate stably for a long time at a higher current density.

[0016] (3) Compared with the hydrothermal amination method, the preparation method of the present invention does not require the use of a special high-pressure reactor, has a relatively weak dependence on production equipment, and has a relatively low operating difficulty and risk. In addition, the heat treatment method and heating method adopted by the present invention can achieve continuous production in actual production.

[0017] (4) Compared with the molten salt method, the preparation method of the present invention does not require the use of a large amount of chloride salt to provide a liquid phase environment, nor does it require additional oxygen and nitrogen sources. The present invention uses an ammonium salt aqueous solution that requires fewer types and amounts of raw materials. The sample prepared after calcination can be used directly without washing. The preparation process is extremely simple and has low technical requirements.

[0018] (5) The present invention can reduce the polarization of the electrode, making the all-vanadium liquid flow battery -2 The energy efficiency reaches over 80% at the current density.

[0019] (6) The present invention does not change the macroscopic structure of the electrode, does not affect the original assembly of the electrode, and does not affect the original battery structure.

[0020] (7) The raw material cost of the present invention is economical, and the experimental process is scalable and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Electron microscope images of electrodes prepared in Comparative Examples 1, 2 and Example 4 of the present invention.

[0022] Figure 2The electrodes prepared in Example 4 and Comparative Example 1 of the present invention are respectively assembled into an all-vanadium redox flow battery at 300 mA cm -2 Comparison of charge and discharge curves under different current densities.

[0023] Figure 3 This is a rate performance diagram of an all-vanadium liquid flow battery assembled using electrodes prepared in Example 4 of the present invention.

[0024] Figure 4 The electrodes prepared in Example 4 of the present invention are used to assemble an all-vanadium redox flow battery at 200 mA cm -2 Long cycle performance diagram at different current densities. DETAILED DESCRIPTION

[0025] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0026] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0027] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0028] Embodiment 1: A method for preparing a modified electrode for an all-vanadium liquid flow battery of the present invention comprises the following steps: (1) The PAN-based graphite felt electrode was immersed in an ammonium carbonate solution until the ammonium salt solution was completely absorbed by the graphite felt electrode. The solvent in the ammonium carbonate solution was distilled water, the surfactant was Tween 40, the concentration of ammonium carbonate was 1.27 mol / L, the total volume of the solvent was fixed at 10 mL, the mass ratio of distilled water to Tween 40 was 1200:1, and the thickness of the PAN-based graphite felt electrode was 4.1 mm and the length and width were 6 cm × 4 cm.

[0029] (2) The PAN-based graphite felt that is fully absorbed with the ammonium carbonate solution in step (1) is placed in a quartz porcelain boat and placed on one side of a quartz tube. When the temperature of the tube furnace rises to 650°C, the graphite felt is pushed into the heat preservation zone for high-temperature activation for 10 min. The atmosphere in the tube furnace is an air atmosphere. After high-temperature activation, a heteroatom-doped high-activity graphite felt electrode, i.e., a modified electrode, can be obtained.

[0030] The modified electrode was used as the negative electrode of the all-vanadium liquid flow battery to test the charge and discharge performance. The positive electrode used untreated original graphite felt and the separator used Nafion 212. The positive and negative electrolytes were both 1.7 M V 3+ +VO 2+ +4.3 M H2SO4, the volume is 45 mL. The charge cut-off voltage is 1.65 V, and the discharge cut-off voltage is 0.8 V. The test results show that at 200 mAcm -2 At the current density, the energy efficiency of the all-vanadium liquid flow battery using the modified electrode composition of this embodiment is 77.47%.

[0031] Embodiment 2: The preparation method of the modified electrode of this embodiment is the same as that of Example 1, the only difference being that the solute in the solution for soaking the PAN-based graphite felt is ammonium sulfate, and the concentration of ammonium sulfate is 0.1 mol / L. Other processes and conditions are the same as those of Example 1.

[0032] The all-vanadium redox flow battery was assembled in the same manner as in Example 1, and the electrochemical performance test was carried out in the same manner. The test results showed that at 200 mA cm -2 At the current density, the energy efficiency of the vanadium battery assembled with the electrode prepared in this example as the negative electrode is 75.62%.

[0033] Embodiment 3: The preparation method of the modified electrode of this embodiment is the same as that of Example 1, the only difference being that the solute in the solution for soaking the PAN-based graphite felt is ammonium sulfate, and the concentration of ammonium sulfate is 0.5 mol / L. Other processes and conditions are the same as those of Example 1.

[0034] The all-vanadium redox flow battery was assembled in the same manner as in Example 1, and the electrochemical performance test was carried out in the same manner. The test results showed that at 200 mA cm -2 At the current density, the energy efficiency of the vanadium battery assembled with the electrode prepared in this example as the negative electrode is 78.53%.

[0035] Embodiment 4: The preparation method of the modified electrode of this embodiment is the same as that of Example 1, the only difference being that the solute in the solution for soaking the PAN-based graphite felt is ammonium sulfate, and the concentration of ammonium sulfate is 1.27 mol / L. Other processes and conditions are the same as those of Example 1.

[0036] The all-vanadium redox flow battery was assembled in the same manner as in Example 1, and the electrochemical performance test was carried out in the same manner. The test results showed that at 200 mA cm -2 At the current density, the energy efficiency of the vanadium battery assembled with the electrode prepared in this example as the negative electrode is 80.17%.

[0037] Embodiment 5: The preparation method of the modified electrode of this embodiment is the same as that of Example 1, the only difference being that the solute in the solution for soaking the PAN-based graphite felt is ammonium nitrate, and the concentration of ammonium nitrate is 1.27 mol / L. Other processes and conditions are the same as those of Example 1.

[0038] The all-vanadium redox flow battery was assembled in the same manner as in Example 1, and the electrochemical performance test was carried out in the same manner. The test results showed that at 200 mA cm -2 At the current density, the energy efficiency of the vanadium battery assembled with the electrode prepared in this example as the negative electrode is 76.80%.

[0039] Embodiment 6: The preparation method of the modified electrode in this embodiment is the same as that in Example 4, the only difference therefrom is that the activation temperature is 850° C., the activation time is 7 min, and the other processes and conditions are the same as those in Example 4.

[0040] The all-vanadium redox flow battery was assembled in the same manner as in Example 1, and the electrochemical performance test was carried out in the same manner. The test results showed that at 200 mA cm -2 At the current density, the energy efficiency of the vanadium battery assembled with the electrode prepared in this example as the negative electrode is 78.4%.

[0041] Embodiment 7: The preparation method of the modified electrode in this embodiment is the same as that in Embodiment 4, the only difference therefrom is that the activation temperature is 950° C., the activation time is 5 min, and the other processes and conditions are the same as those in Embodiment 4.

[0042] The all-vanadium redox flow battery was assembled in the same manner as in Example 1, and the electrochemical performance test was carried out in the same manner. The test results showed that at 200 mA cm -2 At the current density, the energy efficiency of the vanadium battery assembled with the electrode prepared in this example as the negative electrode is 78.14%.

[0043] Comparative Example 1: In this comparative example, PAN-based graphite felt electrodes without any treatment were directly used as the positive and negative electrodes of the all-vanadium liquid flow battery, and the rest of the battery assembly and testing methods were the same as those in Example 1. The test results showed that: at 200 mA cm -2 At the current density, the energy efficiency of the vanadium flow battery is 67.35%.

[0044] Comparative Example 2: The preparation method of the modified electrode of this comparative example is: high temperature activation of a PAN-based graphite felt electrode at 650° C. in an air atmosphere for 10 min to obtain a modified electrode.

[0045] The modified electrode was used as the negative electrode of the vanadium battery, and the positive electrode was an untreated graphite felt electrode. The rest of the battery assembly and testing methods were the same as in Example 1. The test results showed that when the graphite felt electrode treated in this comparative example was used as the negative electrode, the vanadium battery had a high -2 The energy efficiency at this current density is 70.9%.

[0046] Comparative Example 3: The preparation method of the modified electrode of this comparative example is as follows: a PAN-based graphite felt electrode is placed in a 50mL reactor, 15mL of 25% ammonia water is measured, and after fully wetting, it is placed in an oven at 180°C for 15 hours for complete heat preservation, and after cooling, it is washed with distilled water until neutral, and placed in a vacuum oven at 110°C for drying to obtain a modified electrode.

[0047] The modified electrode was used as the negative electrode of the vanadium battery, and the positive electrode was an untreated graphite felt electrode. The rest of the battery assembly and testing methods were the same as those in Example 1. The test results showed that the vanadium battery prepared by using the graphite felt electrode treated in this comparative example as the negative electrode had a high conductivity at 200 mA cm -2 The energy efficiency at the current density is 69.68%.

[0048] Comparative Example 4: The preparation method of the modified electrode of this comparative example is as follows: 2.5 mmol Co(NO3)·6H2O and 20 mmol 2-methylimidazole are dissolved in 50 mL methanol respectively, and the two are mixed after vigorous stirring for 5 min, and the stirring is continued for 30 min to obtain a ZIF-67 solution, and then the graphite felt is immersed in the solution and allowed to stand at room temperature for 18 h and then placed in a 60°C oven for drying for 24 h. Subsequently, the dried graphite felt is calcined at 800°C for 4 h in an argon atmosphere, and finally the calcined graphite felt is cleaned and dried with a mixed solution of hydrochloric acid and FeCl3 to obtain a modified electrode.

[0049] The modified electrode was used as the negative electrode of the vanadium battery, and the positive electrode used an untreated graphite felt electrode. The rest of the battery assembly and testing methods were the same as in Example 1.

[0050] The test results show that the graphite felt electrode treated in this comparative example is used as the negative electrode, and the vanadium battery has a high -2 The energy efficiency at the current density is 74.35%.

[0051] Figure 1The electron microscope images of electrodes prepared in Comparative Examples 1, 2 and Example 4 of the present invention are respectively. The modified graphite felt electrodes in Comparative Examples 1 and 2 have smooth surfaces with almost no morphological changes; while the electrode surface in Example 4 has obvious pore structure, which is essentially a heteroatom-doped electrode based on ammonium salt modification prepared by the method of the present invention, and a large number of pores are formed on the electrode surface, which increases the specific surface area of ​​the electrode and provides abundant active sites.

[0052] like Figure 2 As shown, the electrodes prepared in Example 4 of the present invention and Comparative Example 1 have a high conductivity at 300 mA cm -2 The charge and discharge curve under current density shows that the charge and discharge capacity in Example 1 reaches 1400 mA h, while that in Comparative Example 1 is only about 750 mA h. Compared with the electrode of Comparative Example 1, the all-vanadium liquid flow battery assembled with the electrode prepared in Example 4 has a lower charging voltage and a higher discharge voltage, and a higher capacity, that is, the electrolyte is more fully utilized. Compared with the graphite felt treated in Comparative Example 1, the utilization rate of the electrolyte by the modified electrode in Example 1 is 68.3%, which is 30.5% higher than that of the heat-treated graphite felt electrode in Comparative Example 1.

[0053] like Figure 3 As shown, the rate performance diagram of the all-vanadium liquid flow battery assembled with the electrode prepared in Example 4 of the present invention is as follows: Figure 3 It can be seen that the all-vanadium liquid flow battery assembled with the electrode prepared in Example 4 has excellent battery performance.

[0054] In order to test the long cycle performance of the material under high current density, the electrode material prepared in Example 4 was used as the negative electrode, and the untreated original graphite felt was used as the positive electrode. -2 The charge and discharge cycles were repeated 400 times at a current density of Figure 4 As shown. Figure 4 It can be seen that the efficiency of the battery has basically not decayed after a long cycle, showing excellent stability.

[0055] In summary, the preparation method invented in the present invention is economical and effective, and the prepared high-activity electrode material has good hydrophilicity, conductivity, stable mechanical properties and catalytic properties. The present invention achieves heteroatom doping of electrodes through sudden heat treatment, which not only enriches the number of active sites and increases the reaction specific surface area, but also has a stable structure and excellent performance, greatly reducing the polarization degree of the electrode surface, so that the liquid flow battery can improve its energy efficiency and power density at a higher current density and operate stably, thereby improving the performance of the all-vanadium liquid flow battery in practical applications.

Claims

1. A method for preparing a modified electrode for an all-vanadium redox flow battery, characterized in that: The following steps are involved: (1) Soak the graphite felt electrode in an ammonium salt solution; (2) The graphite felt electrode soaked in ammonium salt in step (1) is placed in a tubular furnace quartz tube for high-temperature activation to obtain a modified electrode.

2. The preparation method according to claim 1, characterized in that In step (2), the graphite felt electrode soaked in ammonium salt is first placed in the non-insulation zone on one side of the quartz tube of the tubular furnace. After the tubular furnace is heated to 500-1000° C., the graphite felt electrode soaked in ammonium salt is pushed into the insulation zone to react for 5-60 minutes.

3. The preparation method according to claim 1, characterized in that In step (1), the ammonium salt solution comprises ammonium salt, surfactant and water, wherein the concentration of the ammonium salt is 0.1-1.5 mol / L, and the mass ratio of the surfactant to water is 1:500-1:2000.

4. The preparation method according to claim 3, characterized in that: The ammonium salt is a soluble ammonium salt, including at least one of ammonium sulfate, ammonium carbonate, ammonium chloride, ammonium nitrate, ammonium phosphate, ammonium fluoride, ammonium bromide, ferrous ammonium sulfate, ammonium molybdate, ammonium tungstate, dodecyltrimethylammonium chloride, tetraethylammonium bromide, and ammonium acetate.

5. The preparation method according to claim 3, characterized in that: The surfactant includes at least one of Tween 20, Tween 40, Span 20, Span 40, and sodium dodecyl sulfate.

6. The preparation method according to claim 1, characterized in that: In step (2), the high temperature activation is carried out in an air atmosphere.

7. The preparation method according to claim 1, characterized in that: In step (1), the graphite felt electrode is polyacrylonitrile-based graphite felt, asphalt-based graphite felt or viscose-based graphite felt.

8. An all-vanadium liquid flow battery, characterized in that: The invention comprises a modified electrode prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing graphene

    CN106006613A

  • Foam carbon and preparation method thereof

    CN109867272A

  • Method for modifying defects of carbon cloth electrode of iron-chromium flow battery

    CN116031418A

  • Biomass modified all-vanadium redox flow battery electrode as well as preparation method and application thereof

    CN116154197A

  • High-catalytic-activity graphite felt electrode for vanadium battery and preparation method of high-catalytic-activity graphite felt electrode

    CN118970073A